Mapping Mathematical Literacy in Combinatorics through Keirsey Temprament Groups and Metacognitive Questions (MQ): A Multiple Case Study of Four Undergraduates - Sinta Verawati Dewi; Rahma Wahyu; Rusdyi Habsyi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
In a combinatorics course, several students still struggle to determine when to use the Multiplication Rule or the Addition Rule, indicating a challenge in mathematical literacy within the context of selection. Meanwhile, there are few studies that map this literacy while simultaneously considering Keirsey's metacognitive questions and temperament in real-world problem-solving situations. This multi-embedded case study research aims to map the mathematical and metacognitive literacy profiles of four students taking a Combinatorics course at a university. Data was collected through an adaptation of the Keirsey Temperament Sorter, one UTS question about breakfast menu choices containing four metacognitive questions (understanding, connection, strategy, and reflection), and semi-structured interviews. Student responses were thematically coded and mapped onto the OECD's formulate–employ–interpret components. The results in this study showed that only Guardian-type students approached a complete literacy profile; Artisan, other Guardian, and Rational types generally only met the initial formulate and interpret component, while employ and advanced interpret were still weak. The implication is that incorporating metacognitive questions into assessments can help lecturers diagnose the need for verification and justification scaffolding that is sensitive to differences in temperament.